2015
DOI: 10.1103/physrevb.91.195119
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer mapping of the paired quantum Hall state: Instability toward anisotropic pairing

Abstract: One of the most dominant candidates for the paired quantum Hall (QH) state at filling factor ν = 5/2 is the Moore-Read (MR) Pfaffian state. A salient problem, however, is that it does not occur exactly at the Coulomb interaction, but rather at a modified interaction, which favors particle-hole symmetry breaking. In an effort to find a better state, in this work, we investigate the possible connection between the paired QH state and the antisymmetrized bilayer ground state, which is inspired by the intriguing i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 107 publications
(184 reference statements)
4
26
0
Order By: Relevance
“…As discussed in the second paragraph of this Article, there are several topologically distinct candidate ground states for the ν = 5/2 FQHS: the Pfaffian 52 , anti-Pfaffian 53,54 , the (3,3,1) Abelian state 55 , a variational wavefunction based on an antisymmetrized bilayer state 56 , the particle-hole symmetric Pfaffian 57,58 , a stripe-like alternation of the Pfaffian and anti-Pfaffian 59 , and other exotic states 60,61 . One thus may consider a potentially large number of topological phase transitions between the pairwise distinct candidate ground states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in the second paragraph of this Article, there are several topologically distinct candidate ground states for the ν = 5/2 FQHS: the Pfaffian 52 , anti-Pfaffian 53,54 , the (3,3,1) Abelian state 55 , a variational wavefunction based on an antisymmetrized bilayer state 56 , the particle-hole symmetric Pfaffian 57,58 , a stripe-like alternation of the Pfaffian and anti-Pfaffian 59 , and other exotic states 60,61 . One thus may consider a potentially large number of topological phase transitions between the pairwise distinct candidate ground states.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative candidate ground states for a FQHS at this filling factor are the anti-Pfaffian 53,54 , the (3,3,1) Abelian state 55 , a variational wavefunction based on an antisymmetrized bilayer state 56 , the particle-hole symmetric Pfaffian 57,58 , a stripe-like alternation of the Pfaffian and anti-Pfaffian 59 , and other exotic states 60,61 . An ongoing intense experimental effort is not yet able to unambiguously discriminate between these gapped candidate states [33][34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations [33][34][35][36] have confirmed that the Abelian (331) Halperin state dominates at vanishing interlayer tunneling (t ⊥ = 0) 14 . Remarkably, through uncovering the underlying pairing nature of the (331) Halperin state 24,25 , it has been suggested that the tunneling effect may drive the system into a non-Abelian phase [16][17][18][26][27][28][29][30][31] , which motivates intensive efforts [36][37][38][39][40] to establish its existence. However, previous numerical studies, primarily utilizing exact diagonalization on small system sizes, are still too limited to reach a consensus.…”
Section: Introductionmentioning
confidence: 99%
“…By using the Dirac description of the dipole nature of CFs, we can identify the paired quantum Hall state of Ref. [21] with PH Pfaffian, and its closeness to anisotropy as a sign of the relevance of anisotropic solutions discussed in Sec. II.…”
Section: Discussionmentioning
confidence: 99%
“…(20) or (21) likely present when considering pairing instabilities in the half-filled LL, consistent with the exact diagonalization results of Refs. [21,22]. Finally, we point out that the Dirac based microscopic wave functions of pairing instabilities have not been proposed and tested yet.…”
Section: Dirac Composite Fermion and Cooper Pairingmentioning
confidence: 99%